Antidiabetic and antihyperlipidemic activity of Piper longum root aqueous extract in STZ induced diabetic rats - Nabi Shaik Abdul; Kasetti Ramesh Babu; Sirasanagandla Swapna; Tilak Thandaiah Krishna; Kumar Malaka Venkateshwarulu Jyothi; Rao Chippada Appa (BMC, 2013)
Abstract Background The available drugs for diabetes, Insulin or Oral hypoglycemic agents have one or more side effects. Search for new antidiabetic drugs with minimal or no side effects from medicinal plants is a challenge according to WHO recommendations. In this aspect, the present study was undertaken to evaluate the antihyperglycemic and antihyperlipidemic effects of Piper longum root aqueous extract (PlrAqe) in streptozotocin (STZ) induced diabetic rats. Methods Diabetes was induced in male Wister albino rats by intraperitoneal administration of STZ (50 mg/kg.b.w). Fasting blood glucose (FBG) levels were measured by glucose-oxidase & peroxidase reactive strips. Serum biochemical parameters such as glycosylated hemoglobin (HbA1c), total cholesterol (TC), triglycerides (TG), very low density lipoprotein (VLDL), low density lipoprotein (LDL) and high density lipoprotein (HDL) cholesterol were estimated. The activities of liver and kidney functional markers were measured. The statistical analysis of results was carried out using Student t-test and one-way analysis (ANOVA) followed by DMRT. Results During the short term study the aqueous extract at a dosage of 200 mg/kg.b.w was found to possess significant antidiabetic activity after 6 h of the treatment. The administration of aqueous extract at the same dose for 30 days in STZ induced diabetic rats resulted in a significant decrease in FBG levels with the corrections of diabetic dyslipidemia compared to untreated diabetic rats. There was a significant decrease in the activities of liver and renal functional markers in diabetic treated rats compared to untreated diabetic rats indicating the protective role of the aqueous extract against liver and kidney damage and its non-toxic property. Conclusions From the above results it is concluded that the plant extract is capable of managing hyperglycemia and complications of diabetes in STZ induced diabetic rats. Hence this plant may be considered as one of the potential sources for the isolation of new oral anti hypoglycemic agent(s).